2008
DOI: 10.1088/1741-2560/5/2/007
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial current stimulation focality using disc and ring electrode configurations: FEM analysis

Abstract: We calculated the electric fields induced in the brain during transcranial current stimulation (TCS) using a finite-element concentric spheres human head model. A range of disc electrode configurations were simulated: (1) distant-bipolar; (2) adjacent-bipolar; (3) tripolar; and three ring designs, (4) belt, (5) concentric ring, and (6) double concentric ring. We compared the focality of each configuration targeting cortical structures oriented normal to the surface ('surface-radial' and 'cross-section radial')… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
242
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 292 publications
(255 citation statements)
references
References 98 publications
10
242
1
1
Order By: Relevance
“…As a general rule, increasing 4x1 ring diameter will increase the depth of penetration and maximum intensity under the ring 28 . Conversely, reducing ring radius increases focality but decreases induced brain electric field.…”
Section: Possible Modificationsmentioning
confidence: 95%
“…As a general rule, increasing 4x1 ring diameter will increase the depth of penetration and maximum intensity under the ring 28 . Conversely, reducing ring radius increases focality but decreases induced brain electric field.…”
Section: Possible Modificationsmentioning
confidence: 95%
“…Current-flow modeling approaches range from spherical models (Rush and Driscoll, 1969;Ferdjallah et al, 1996;Stecker, 2005;Miranda et al, 2006;Datta et al, 2008;Dmochowski et al, 2012) to more realistic individualized models derived from MRI (Wagner et al, 2004;Datta et al, 2009;Sadleir et al, 2010;Parazzini et al, 2011;Minhas et al, 2012;Datta et al, 2010;Wagner et al, 2007). Individualized modeling implies the need to consider the anatomy of individual subjects , in particular for patient populations that may have abnormal brain anatomy Dmochowski et al, 2013).…”
Section: Guidelines For Modelingmentioning
confidence: 99%
“…The current direction in the brain was predominantly radial under the electrode and tangential between electrodes. Datta also used a FE spherical head model to study the focality of different combinations of disc and ring electrodes [35] and found that decreasing electrode separation improved focality but increased shunting through the scalp. Use of more than two disc electrodes or of ring electrodes allowed increasing focality in the sense that the current density could be made higher under one electrode and lower under the others.…”
Section: Spatial Distribution Of Electric Fieldmentioning
confidence: 99%